Strategi Peningkatan Pelayanan Air Minum Di Kelurahan Buntusu Kota Makassar - Dandi Risno; Fuad Azis; Rimba Arief (Journal of Urban Planning Studies, 2022)
The purpose of this study was to determine community satisfaction with water services in Buntusu Village, namely with water services and water quantity which had a significant effect so that community satisfaction with water services was tested using qualitative descriptive analysis tools and quantitative descriptive analysis using linear regression method. Factors that have a direct and significant effect on community satisfaction from the results of linear regression analysis, there are 2 stimulants of drinking water services (X1), and the quantity of drinking water (X3) the results are accepted meaning that it does not significantly affect community satisfaction. While the factors that do not have a direct significant effect on community satisfaction from the results of linear regression analysis, there are two, namely stimulants of drinking water quality (X2) and drinking water continuity (X4), then the results are rejected, meaning that they have a significant effect on community satisfaction.